1981
DOI: 10.5703/1288284314032
|View full text |Cite
|
Sign up to set email alerts
|

Highway Bridge Vibration Studies

Abstract: The attached Final Report "Highway Bridge Vibration Studies" is submitted as a summary of the extensive research conducted on this project. The research has provided considerable new information and clearer understanding of the bridge vibration problem and advanced capability toward the use of a dynamic-based design criterion for highway bridges. Such use should provide more effectively for the comfort of users of bridges in an economic and beneficial manner.This research in our opinion has been very productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Psychological discomfort results from unexpected motions, but physiological discomfort results from a low frequency, high amplitude vibration such as sea sickness (Roeder, Barth and Bergman 2002). Some of the earliest measurements concerning human sensitivity to vibrations were carried out by Mallock in 1902 (Gaunt and Sutton 1981). Investigating complaints of unpleasant vibration caused by passing traffic to certain house near Hyde Park, Gaunt and Sutton (1981) concluded that the acceleration caused noticeable discomfort is one per cent of the gravitational acceleration.…”
Section: Vibration Acceleration Of the Vehiclementioning
confidence: 99%
“…Psychological discomfort results from unexpected motions, but physiological discomfort results from a low frequency, high amplitude vibration such as sea sickness (Roeder, Barth and Bergman 2002). Some of the earliest measurements concerning human sensitivity to vibrations were carried out by Mallock in 1902 (Gaunt and Sutton 1981). Investigating complaints of unpleasant vibration caused by passing traffic to certain house near Hyde Park, Gaunt and Sutton (1981) concluded that the acceleration caused noticeable discomfort is one per cent of the gravitational acceleration.…”
Section: Vibration Acceleration Of the Vehiclementioning
confidence: 99%
“…The target of this work is small and medium span bridges (up to 50 m) on most of the highways which are concrete beam structures. An extensive study was conducted by Gaunt and Sutton (1981) and reported bridge frequency and acceleration levels for 62 bridges. The bridges were of span less than 30 meters.…”
Section: Low Frequency and Low Acceleration Vibration Energy Harvementioning
confidence: 99%
“…Among them, deflection limits are the most commonly used by design engineers because calculation of deflection is easier and more convenient than calculation of the other studied characteristics. However, many previous studies have found that humans are more sensitive to acceleration than to displacement (Gaunt, 1981), that deflection limits alone are a poor method for controlling bridge vibrations or ensuring human comfort (Wright and Walker, 1971), that vibration cannot be consistently prevented by a simple deflection limit alone (Oehler, 1970), and that deflection limits do not mitigate the vibration and acceleration that induce human reactions (Fountain and Thunman, 1987). In recent years, significant research has occurred on serviceability of bridges.…”
Section: Introductionmentioning
confidence: 97%